Intravascular embolization with spinal decompression and vertebral shaping for acute cauda equina syndrome from aggressive vertebral hemangioma: a case report and literature review - Chen, Qing-Quan; Wang, Hong-Shen; Wang, Hui; Chen, Jin-Shui; Xiao, Jie; Yang, Xiu (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the clinical outcomes of a multidisciplinary approach for the treatment of aggressive vertebral hemangioma with acute cauda equina compression.Case descriptionA 37-year-old female patient with aggressive vertebral hemangioma presented with sudden loss of muscle strength in both lower limbs (grade I–II) and difficulty in urination and defecation. Magnetic resonance imaging and digital subtraction angiography confirmed a vascular tumor within and around the L4 vertebra, causing cauda equina compression. The treatment involved staged vascular embolization (of the third lumbar artery and branches of the sacral artery) combined with L4 vertebroplasty, laminectomy decompression, and pedicle screw fixation. Postoperative pain was immediately relieved. After 3 months of rehabilitation, muscle strength in both lower limbs recovered to grade 3, with significant improvement in spontaneous urination and defecation. Imaging studies showed complete relief of spinal canal compression.ConclusionsAggressive spinal hemangioma may require multidisciplinary collaboration, and staged vascular embolization combined with spinal decompression and stabilization surgery can effectively improve neurological function. Early intervention is crucial for achieving favorable outcomes.